2019
DOI: 10.1002/jcla.23023
|View full text |Cite
|
Sign up to set email alerts
|

Longnon‐coding RNA NEAT1 overexpression associates with increased exacerbation risk, severity, and inflammation, as well as decreased lung function through the interaction with microRNA‐124 in asthma

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractBackground: This study aimed to explore the association of long non-coding RNA nuclear-enriched abundant transcript 1 (lncRNA NEAT1) with exacerbation risk, lung function, and inflammatory cytokines in asthma. Methods:A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…Jin et al ( 29 ) found that NEAT1 promoted liver fibrosis by mediating miR-506 and transcriptional activator GLI3. In addition, NEAT1 has been found to impair lung function through the interaction with miR-124 ( 30 ). Understanding the crosstalk between lncRNA, miRNA and mRNA, and their regulatory pattern could provide a novel perspective for the therapy of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al ( 29 ) found that NEAT1 promoted liver fibrosis by mediating miR-506 and transcriptional activator GLI3. In addition, NEAT1 has been found to impair lung function through the interaction with miR-124 ( 30 ). Understanding the crosstalk between lncRNA, miRNA and mRNA, and their regulatory pattern could provide a novel perspective for the therapy of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs have been revealed to act as a modulator of Th1 and Th2 inflammation in asthma. Li et al (2020) confirmed that lncRNA NEAT1 was upregulated and were negatively correlated with miR-124. Also, it was positively correlated with Th1-associated TNF-α, IL-1β and Th17-associated IL-17 to enhance the exacerbation risk of asthma, which showed its potential to regulate Th1 inflammation in asthma.…”
Section: Lncrnas Associated With Inflammation In Asthma Pathogenesismentioning
confidence: 64%
“…To determine the role of lncRNAs in autophagy, we tested six candidate lncRNAs (FER1L4, HIF1A-AS1, MIR22HG, NEAT1, H19, and MIAT) supposed to be involved in the process of inflammation. 19,[33][34][35][36][37] Among them, H19, a conserved lncRNA, was the most differentially expressed. H19 has been reported to regulate autophagy in various types of cancer, and its aberrant expression was associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%